Comparative Study of Low Pressure versus Standard Pressure Carbon Dioxide Pneumoperitoneum in Reducing Shoulder Tip Pain Post Laparoscopic Cholecystectomy - Thapa, Pradip; Thapa, Divas; Sharma, Anup (Journal of Nepalgunj Medical College, 2022)
Introduction: Laparoscopic cholecystectomy is the gold standard treatment for cholelithiasis. Postoperative shoulder tip pain is common complaint. Evidences suggest that using low pressure pneumoperitoneum (8-10 mmHg) during the procedure rather than standard pressure (12-14 mmHg) decreases the incidence and severity of shoulder tip pain without compromising working space. Aims: The aim of this study was to evaluate the impact of low pressure and standard pressure pneumoperitoneum on shoulder tip pain post laparoscopic cholecystectomy. Methods: A prospective hospital based study conducted at Nepalgunj Medical College, Kohalpur from January 2019 to December 2020. Hundred patients were enrolled, fifty each in “low pressure carbondioxide pneumoperitoneum” and “standard pressure carbondioxide pneumoperitoneum” groups, who underwent laparoscopic cholecystectomy. The two groups were compared in terms of incidence and severity of shoulder tip pain, surgeon’s satisfaction score, top-up analgesia requirement, procedural time, conversion to standard pressure, intraoperative complications and length of hospital stay. Results: There were 45 (90%) females and five (10%) males in low pressure group and 44 (88%) females and six (12%) males in standard pressure group. Fourteen (28%) patients in low pressure and 32 (64%) patients in standard pressure group had shoulder tip pain (p=0.001). The severity of shoulder tip pain was less in low pressure group and was significant at eight hours (p=0.006) and 12 hours (p=0.008). Top-up analgesia was required more in standard pressure group. There were no intraoperative complications but only one conversion to standard pressure. Surgeon’s satisfaction score, conversion to open cholecystectomy and procedural time were comparable in both groups with shorter hospital stay in low pressure group. Conclusion: Low pressure carbondioxide pneumoperitoneum is safe and effective strategy in reducing incidence and severity of shoulder tip pain after laparoscopic cholecystectomy.